2013
DOI: 10.1136/postgradmedj-2012-101350rep
|View full text |Cite
|
Sign up to set email alerts
|

Republished: Environmental and occupational exposure to chemicals and telomere length in human studies

Abstract: Telomeres are complexes of tandem repeats of DNA (5'-TTAGGG-3') and protein that cap eukaryotic chromosomes and play a critical role in chromosome stability. Telomeres shorten with aging and this process can be accelerated by increased oxidative stress and episodes of inflammation. Evidence is rapidly growing that telomere length (TL) may be affected by environmental chemicals that have frequently been associated with chronic diseases. In this article, we review the published data on TL in relation to environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Several of these environmental factors may be seen as stressors in the sense that they trigger an integrated stress response, that is a physiological and behavioural change that ensure survival in return for a physiological cost (Romero ). Although the stress response was not always explicitly measured, stress‐induced telomere attrition was suggested by numerous recent reviews of epidemiological studies in humans; these studies highlighted negative correlations between telomere length and psychological stress (Epel et al ; Kiecolt‐Glaser & Glaser ; Lin et al ; Price et al ; Law et al ) but also dietary patterns (Freitas‐Simoes et al ; Rafie et al ), pre‐natal exposure to stressors, health‐risk behaviours (Shalev et al ; Astuti et al ) and exposure to chemicals (Zhang et al ). Five recent meta‐analyses confirmed the negative effect of different kinds of stressors on telomere length and shortening in humans (effect sizes from − 0.06 to − 0.25; Schutte & Malouff , ; Mathur et al ; Oliveira et al ; Pepper et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these environmental factors may be seen as stressors in the sense that they trigger an integrated stress response, that is a physiological and behavioural change that ensure survival in return for a physiological cost (Romero ). Although the stress response was not always explicitly measured, stress‐induced telomere attrition was suggested by numerous recent reviews of epidemiological studies in humans; these studies highlighted negative correlations between telomere length and psychological stress (Epel et al ; Kiecolt‐Glaser & Glaser ; Lin et al ; Price et al ; Law et al ) but also dietary patterns (Freitas‐Simoes et al ; Rafie et al ), pre‐natal exposure to stressors, health‐risk behaviours (Shalev et al ; Astuti et al ) and exposure to chemicals (Zhang et al ). Five recent meta‐analyses confirmed the negative effect of different kinds of stressors on telomere length and shortening in humans (effect sizes from − 0.06 to − 0.25; Schutte & Malouff , ; Mathur et al ; Oliveira et al ; Pepper et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has used telomere length (TL), a common biomarker of biological aging [10], to characterize the relationship between particle exposures and aging. Nevertheless, data on the associations between ambient particles and TL have been conflicting and thus reflect a need for alternative biological aging markers [6, 11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…In humans, telomere erosion can be accelerated by different environmental factors such as exposure to pollutants (Zhang et al, 2013). For instance, it has been reported that outdoor workers exposed to traffic pollution have shorter telomeres than indoor office workers (Hoxha et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, women telomere length decreases as exposure to pollution caused by hazardous wastes increases (De Felice et al, 2012). One underlying mechanism that could potentially explain accelerated telomere shortening is oxidative stress (Von Zglinicki et al, 2000;Zhang et al, 2013). This corresponds to the imbalance between the production of reactive oxygen species (ROS) and the antioxidant capacity of an organism (Finkel and Holbrook, 2000).When metabolic by-products, such as ROS, are not fully neutralized by anti-oxidant defenses, they may oxidize cellular macromolecules such as DNA (Houben et al, 2008).…”
Section: Introductionmentioning
confidence: 99%